Palmitoylethanolamide reduces granuloma-induced hyperalgesia by modulation of mast cell activation in rats - Cinelli Maria Pia; Palazzo Enza; Cipriano Mariateresa; Luongo Livio; De Filippis Daniele; de Novellis Vito; Maione Sabatino; Iuvone Teresa (SAGE Publishing, 2011)
Abstract The aim of this study was to obtain evidences of a possible analgesic role for palmitoylethanolamide (PEA) in chronic granulomatous inflammation sustained by mast cell (MC) activation in rats at 96 hours. PEA (200-400-800 μg/mL), locally administered at time 0, reduced in a concentration-dependent manner the expression and release of NGF in comparison with saline-treated controls. PEA prevented nerve formation and sprouting, as shown by histological analysis, reduced mechanical allodynia, evaluated by Von Frey filaments, and inhibited dorsal root ganglia activation. These results were supported by the evidence that MCs in granuloma were mainly degranulated and closely localized near nerve fibres and PEA significantly reduced MC degranulation and nerves fibre formation. These findings are the first evidence that PEA, by the modulation of MC activation, controls pain perception in an animal model of chronic inflammation, suggesting its potential use for the treatment of all those painful conditions in which MC activation is an initial key step.